(untitled) (CIPEEX, 2025)
Introduction: The rational use of medicines is directly related to the quality of prescription and dispensing practices. Inadequate prescriptions and failures in dispensing processes may compromise patient safety, therapeutic effectiveness, and health system sustainability. Objective: To review the literature on evaluation methods and outcomes related to prescription and dispensing of medicines in healthcare services. Methods: This is an integrative literature review using the PICO strategy. Studies published in the last five years, with a cross-sectional or descriptive design, in English or Portuguese, were included. Searches were conducted in PubMed, SciELO, and Google Scholar using the descriptors: Prescription AND Dispensing AND Medicines AND Evaluation. Results: From 42 studies identified, 7 met the inclusion criteria. The main problems reported were polypharmacy, incomplete or inappropriate prescriptions, lack of patient counseling, and failures in pharmacovigilance records. Conversely, interventions such as clinical pharmacy services, electronic prescribing systems, and continuing education for professionals demonstrated positive impacts on safety and rational medicine use. Conclusion: Evaluating prescription and dispensing practices is essential for improving patient safety, optimizing resources, and strengthening rational medicine use policies.